Makna Kata Buruj dalam Al-Qur’an Perspektif Pengamatan Astronomis - Firdaus, Muhammad Dimas; Putraga, Hariyadi; Hidayat, Muhammad; Rakhmadi, Arwin Juli (Universitas Islam Negeri Mataram, 2023)
Al-Qur’an as the holy book of Muslims contains many themes of discussion in it, ranging from faith, sharia, stories and science. One of the discussions related to science is assembling celestial bodies. Buruj is one of the celestial bodies mentioned in Al-Qur'an, in total there are three verses that discuss the buruj as a celestial body. In some literature, buruj is interpreted as a big star, a big planet, a constellation, and a set of stars. From these meanings, a common thread can be drawn that the buruj is understood as a set of stars. In the previous research used an interpretive perspective, this paper tries to understand the meaning of the buruj more broadly by using the perspective of astronomical observations conducted by the OIF UMSU team. From the observations, it is known that there are several types of sets of stars, such as constellations, open star clusters, globular star clusters, and galaxies. So that the meaning of the buruj in the Qur'an as a celestial body is a set of beautiful stars that humans can observe, not limited to the constellations which number 12, 48 or 88.